2016
DOI: 10.1038/srep31651
|View full text |Cite
|
Sign up to set email alerts
|

Up- regulation of miR-328-3p sensitizes non-small cell lung cancer to radiotherapy

Abstract: MicroRNAs (miRNAs) are believed to be resistant against radiotherapy in certain types of cancers. The aim of our study was to determine the clinical application of miRNAs in non-small cell lung cancer (NSCLC). Sixty NSCLC tissue samples and adjacent histologically normal tissues were obtained for miRNAs microarray analysis and validated by RT-qPCR. Correlation between miRNA expression level and clinicopathological features was evaluated. Our study examined the influence of changed miRNA expression on the damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…Moreover, miR-328, which interacts with PDLIM5, has Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry been found downregulated in multiple cancers. miR-328 inhibits the survival of cancer cells and enhances the sensitivity of cancer to radiotherapy [29,30]. Furthermore, overexpression of miR-328 reversed drug resistance and inhibited cell invasion of cancer stem cell-like SP cells in colorectal cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-328, which interacts with PDLIM5, has Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry been found downregulated in multiple cancers. miR-328 inhibits the survival of cancer cells and enhances the sensitivity of cancer to radiotherapy [29,30]. Furthermore, overexpression of miR-328 reversed drug resistance and inhibited cell invasion of cancer stem cell-like SP cells in colorectal cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…21 Changes in metabolism driven by oncogenes are capable of controlling tumour growth through regulation of oxygen consumption. 22 enhance the radiosensitivity of non-small cell lung cancer cells 23 and osteosarcoma. 24 Moreover, miR-328-3p exerts as an anti-tumour miR with potential impeding osteosarcoma cell migration through regulation of MMP16.…”
Section: Discussionmentioning
confidence: 99%
“…gastric cancer (18), hepatocellular carcinoma (19), prostate cancer (20), renal cell carcinoma (21), glioma (22) and lung cancer (23). Moreover, numerous studies reported that the dysregulation of miRNAs is involved in tumorigenesis and tumor development; some miRNAs act as an oncogene or tumor suppressor gene in human cancers, depending on the regulated tumor forms and their specific target genes (24).…”
Section: Microrna-379 Acts As a Tumor Suppressor In Non-small Cell Lumentioning
confidence: 99%